Hubungan Peran Petugas Kesehatan dan Dukungan Suami dengan Kepatuhan Ibu Nifas Untuk Melakukan Perawatan Payudara - Rahmadhani, Sendy Pratiwi; Amalia, Rizki (JOURNAL OF MIDWIFERY SCIENCE, 2025)
Breast care is a way of caring for the breasts that is carried out during pregnancy or the puerperium for milk production, in addition to breast hygiene and the shape of the nipple that goes inward or flat. to find out the relationship between the role ofhealth workers, sources of information and husband's support with postpartum mothers' compliance with breast care. Thisstudy uses a quantitative analytical survey research design with a cross sectional approach. The population in this studywere all postpartum mothers who visited. The sample of this study was 80 respondents who were taken in a non-random wayusing the accidental sampling method. The analysis used is univariate analysis and bivariate analysis. From the results of the chi-square statistical test, on the variable of the role of health workers obtained p-value 0.002 (< = 0.05), husband's support obtained p-value 0.001 (< = 0.05), meaning that there is a significant health workers and husband's support with breast care duringthe puerperium. There is a relationship between the role of health workers and husband's support with postpartum mothers' adherence to breast care